Effect of Calcined Eggshell Particles on Some Properties and Microstructure of Al-Si-Mg Alloy - Eze, S. C.; Yawas, D. S; Dauda, E. T. (Journal of Scientific Research, 2024)
In this study, different sizes (25, 50, and 75 µm) and volume fractions (1, 2, and 3 wt%) of calcined eggshell particles were utilized to strengthen the Al-Si-Mg alloy. Several experimental runs were conducted to assess the impact of particle size and concentration on both physical properties (density, corrosion, and thermal conductivity) and mechanical properties (hardness, yield strength, impact energy, and modulus of elasticity). The findings revealed significant enhancements in hardness (21 %), yield strength (61 %), modulus of elasticity (43 %), and thermal conductivity (34 %). Conversely, a reduction of 62 % in impact strength and 8 % in density was observed. The corrosion rate displayed an increase from 0 to 16.67 mpy. Analysis using XRD and XRF techniques identified CaO and Al2O3 as the primary constituents of the eggshell. Optical micrographs consistently showed cored (segregated) dendritic structures typical of castings cooled under normal conditions in the Al-Si-Mg composite. SEM micrographs, EDS spectra, and area analyses confirmed a uniform distribution of Calcined Eggshell Particles (CEP) within the composite films. Additionally, an optimal calcination condition for the eggshell particles was determined to be 900 °C for 2.5 h, resulting in a CaO yield of 99.62 %.